2011
DOI: 10.1037/a0024595
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness training increases momentary positive emotions and reward experience in adults vulnerable to depression: A randomized controlled trial.

Abstract: MBCT is associated with increased experience of momentary positive emotions as well as greater appreciation of, and enhanced responsiveness to, pleasant daily-life activities. These changes were unlikely to be pure epiphenomena of decreased depression and, given the role of positive emotions in resilience against depression, may contribute to the protective effects of MBCT against depressive relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
270
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(304 citation statements)
references
References 55 publications
22
270
0
5
Order By: Relevance
“…Initial evidence suggests it may be possible to alter reward processing with psychological therapies Geschwind et al 2011). Incorporating strategies to boost effective reward responding into such preventive interventions may be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Initial evidence suggests it may be possible to alter reward processing with psychological therapies Geschwind et al 2011). Incorporating strategies to boost effective reward responding into such preventive interventions may be worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Para o diagnóstico de depressão maior, o número e estado atual de episódios depressivos foi utilizado a entrevista clínica estruturada e os critérios para episódio depressivo do DSM-IV (APA, 2000; Godfrin & Heeringen, 2010;Bieling et al, 2012;Williams et al, 2014) Godfrin & Heeringen, 2010;Williams et al, 2014;Van Aalderen, 2011;Forkmann et al, 2014;Geschwind et al, 2011;Geschwind et al, 2012;Radford et al, 2014;Segal et al, 2010). Para a avaliação da severidade dos sintomas residuais depressivos foram utilizados a escala de Hamilton (Godfrin & Heeringen, 2010;Bieling et al, 2012 ;Williams et al, 2014;Van Aalderen, 2011;Forkmann et al, 2014;Geschwind et al, 2011;Geschwind et al, 2012;Segal et al, 2010;Hamilton,1960) e/ou o Inventário de Beck (Godfrin & Heeringen, 2010;Williams et al, 2014;Van Aalderen, 2011;Radford et al, 2014;Beck, 1961).…”
Section: Instrumentosunclassified
“…Para a avaliação da severidade dos sintomas residuais depressivos foram utilizados a escala de Hamilton (Godfrin & Heeringen, 2010;Bieling et al, 2012 ;Williams et al, 2014;Van Aalderen, 2011;Forkmann et al, 2014;Geschwind et al, 2011;Geschwind et al, 2012;Segal et al, 2010;Hamilton,1960) e/ou o Inventário de Beck (Godfrin & Heeringen, 2010;Williams et al, 2014;Van Aalderen, 2011;Radford et al, 2014;Beck, 1961).…”
Section: Instrumentosunclassified
See 1 more Smart Citation
“…Several studies support the thesis that mindfulness training can influence emotion regulation. For example, participants of mindfulness training programs have reported, subsequently, a decrease in difficulty in regulating their own emotions (Robins, Keng, Ekblad, & Brantley, 2012), a reduction of intensity and frequency of negative feelings (Chambers et al, 2008;Zeidan, Johnson, Gordon, & Goolkasian, 2010) as well as an increase in positive feelings (Geschwind, Peeters, Drukker, van Os, & Wichers, 2011;Jain et al, 2007;Tang et al, 2007). Furthermore, it has been shown that mindfulness training can reduce the detrimental effect of emotional interference on performance in cognitive tasks (Ortner, Kilner, & Zelazo, 2007).…”
Section: Introductionmentioning
confidence: 99%